Poly[dimethylammonium [tris(mu(2)-formato-kappa O-2:O `)cadmate(II)]] - Gao, S.; Ng, S.W. (International Union of Crystallography, 2010)
In the coordination polymer, {(C2H8N)[Cd(CHO2)(3)]}(n), the Cd-II atom lies on a special position of (3) over bar site symmetry in an octahedron of O atoms. The formate unit bridges the metal atoms, generating a three-dimensional polyanionic framework. The disordered cations occupy the cavities within the framework, and are N-H center dot center dot center dot O hydrogen-bonded to the framework.